The bee genus colletes latreille, 1802 (Hymenoptera: Apoidea: Colletidae) in West Africa - Kuhlmann, M.; Goergen, G. (2025)
Bee species of the genus Colletes Latreille are revised for West Africa. In total four species are recorded from this area with one described as new: Colletes aragorn Kuhlmann sp. nov.. An illustrated key is provided to facilitate species identification.